2012
DOI: 10.1111/j.1537-2995.2012.03595.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemotherapy bedside biovigilance involving vital sign values and characteristics of patients with suspected transfusion reactions associated with fluid challenges: can some cases of transfusion‐associated circulatory overload have proinflammatory aspects?

Abstract: Trend monitoring of peritransfusion VSVs, especially blood pressures, may aid in the bedside recognition of TACO/FC-STRs. A subset of these patients may also present with febrile and/or inflammatory signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 29 publications
(54 reference statements)
2
80
2
1
Order By: Relevance
“…1,8 However, there are little aggregate data available to help determine whether changes in vital signs resulting from transfusion are physiologic or, rather, suggestive of a possible adverse event. 3 Therefore, we undertook a comprehensive study examining the variation in commonly recorded vital signs (i.e., temperature, heart rate, and blood pressure) to better understand: 1) the physiologic variations associated with these variables across all blood components issued at our facility and 2) whether transfusion reactions were being reported in compliance with institutional guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8 However, there are little aggregate data available to help determine whether changes in vital signs resulting from transfusion are physiologic or, rather, suggestive of a possible adverse event. 3 Therefore, we undertook a comprehensive study examining the variation in commonly recorded vital signs (i.e., temperature, heart rate, and blood pressure) to better understand: 1) the physiologic variations associated with these variables across all blood components issued at our facility and 2) whether transfusion reactions were being reported in compliance with institutional guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent published study of recipient vital signs during uncomplicated transfusion considered fewer than 150 patients and primarily examined individuals receiving RBC infusions. 3 Data regarding variation of vital signs following uncomplicated plasma or platelet (PLT) product administration are almost nonexistent in the medical literature. 4,5 Some limited data are available regarding hematopoietic progenitor cell infusion rates, but the applicability of these products to whole blood-derived components is unknown.…”
mentioning
confidence: 99%
“…Subsequently, Andrzejewski et al reported approximately 65% of patients with TACO exhibited an inflammatory or febrile component with their clinical presentation 32,33 . Similar findings were also reported by the Quebec Hemovigilance System 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Although no mandated vital sign value magnitude thresholds are “officially” designated by the blood bank for the bedside recognition/reporting of STRs, information regarding the commonly used 1°C/2°F observation for the identification of a febrile reaction is included in the annual required training of nurses about transfusions. It is repeatedly stressed to nurses and physicians, as well as being noted in pertinent clinical policies regarding HT, however, that such information should be viewed only in the larger context of the clinical status of the patient, supplementing the practitioner's own clinical judgment during bedside monitoring, and that based on published literature examining vital sign values in patients undergoing uncomplicated transfusions, clinically stable patients should experience few if any changes from baseline vital sign values . In situations in which some providers may be uncertain/unwilling to attribute the patient's clinical changes to the HT, nurses at the bedside are empowered by a directive from the blood bank medical director to order an STR evaluation.…”
Section: Methodsmentioning
confidence: 99%